Risk factors for pediatric cerebral sinovenous thrombosis: A case-control study with case validation. Issue 194 (October 2020) - Sellers, Austin; Meoded, Avner; Quintana, Javier; Jallo, George; Amankwah, Ernest; Nguyen, Anh Thy H.; Betensky, Marisol; Mills, Katie; Goldenberg, Neil; Shimony, Nir
Abstract: Introduction: Cerebral sinovenous thrombosis (CSVT) represents the second most common type of venous thromboembolism (VTE) in children. Current literature includes limited evidence on risk factors for CSVT, particularly in the pediatric population. We sought to determine risk factors for CSVT in pediatric patients through a single-institutional case-control study. In addition, we evaluated thrombophilias, treatments and outcomes in CSVT among cases. Methods: A case-control study was performed at Johns Hopkins All Children's Hospital on patients admitted from March 31, 2006 through April 1, 2018. Cases were identified using diagnostic codes and confirmed based on electronic health record (EHR) and neuroimaging review. Controls were matched in a 2:1 fashion accounting for the month and year of admission. Results: A total of 60 CSVT cases and 120 controls were identified. Median (range) age was 4.8 years (0–21.3 years) for cases and 5.6 years (0–20.0 years) for controls. Factors putatively associated with CSVT in unadjusted analyses were: corticosteroid use, presence of a central venous catheter, mechanical ventilation, systemic infection, head/neck infection, head/neck trauma, and chronic inflammatory disease. In the multivariable model, head/neck infection (OR: 13.8, 95% CI: 4.87–38.7; P < 0.01), head/neck trauma (OR: 12.7, 95% CI: 2.88–56.2; P < 0.01), and mechanical ventilation (OR: 9.32, 95% CI: 2.35–36.9; P = 0.01) remained independent, statistically-significant risk factors. 61% of patients were subacutely treated with anticoagulants and of those, only two developed relevant bleeding after initiation of therapy. Conclusions: This single-institutional case-control study reveals that head/neck infection, head/neck trauma, and mechanical ventilation are independent risk factors for pediatric CSVT. These findings will be further investigated via a cooperative registry of pediatric hospital-acquired VTE, by which a risk model for pediatric CSVT will be developed and validated, in order to inform future preventive strategies in at-risk pediatric patients. Highlights: Cerebral Sinovenous Thrombosis is a common type of venous thromboembolism in children. Risk factors for developing CSVT in children have not been established via published case:control studies. Head/neck infection, head/neck trauma and mechanical ventilation were found as independent risk factors for pediatric CSVT. These findings will be substantiated and further investigated via a multicenter registry on pediatric venous thromboembolism.